Using Technology to Increase the Use of Evidence-Based Behavioral Interventions With Students With High-Incidence Disabilities. Issue 3 (September 2021) - Riden, Benjamin S.; Kumm, Skip; Jolivette, Kristine
Educators of students with disabilities who frequently display challenging behaviors are expected to deliver high-leverage practices and evidence-based behavioral interventions to improve student academic engagement and appropriate behaviors. For these practices and interventions to be successful, educators need innovative, accessible, and sustainable tools to efficiently and effectively implement these practices and interventions as part of their classroom and behavior management routines. Using technology as a delivery platform can fit this need. The Journal of Special Education Technology special issue presents three experimental studies where teachers used technology to deliver behavioral interventions and one qualitative study examining teachers' perspectives of using technology for behavior management.